2020
DOI: 10.1101/2020.10.21.349373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and immunogenicity of different BCG doses in BALB/c and CB6F1 mice when challenged with H37Rv or Beijing HN878

Abstract: In this study, 2 strains of mice (BALB/c and CB6F1) were vaccinated with a range of Bacille Calmette Guerin (BCG) Danish doses from 300,000 to 30 CFU/mouse, followed by either immunogenicity evaluation or aerosol infection with Mycobacterium tuberculosis (a laboratory strain H37Rv or West-Beijing HN878 strain). The results indicated that both strains of mice when infected with HN878 exhibited significant protection in their lungs with BCG doses at 300,000 to 3000 CFU (BALB/c) and 300,000 to 300 CFU (CB6F1). Wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…First, unlike our previous report, we found that wild-type BCG conferred protection against Mtb M2 infection 31 . Potential explanations include the following: (1) the inoculation dose of BCG was different between the work of Gröschel et al 59 and the current study, as it has been reported that the efficacy and immunogenicity were differentially affected according to the BCG dose. (2) This could also be the result of using different parental BCG strains (ATCC 35734 in this study versus BCG Pasteur 1173P2 kindly provided by Dr Brosch).…”
Section: Discussionmentioning
confidence: 68%
“…First, unlike our previous report, we found that wild-type BCG conferred protection against Mtb M2 infection 31 . Potential explanations include the following: (1) the inoculation dose of BCG was different between the work of Gröschel et al 59 and the current study, as it has been reported that the efficacy and immunogenicity were differentially affected according to the BCG dose. (2) This could also be the result of using different parental BCG strains (ATCC 35734 in this study versus BCG Pasteur 1173P2 kindly provided by Dr Brosch).…”
Section: Discussionmentioning
confidence: 68%